1992
DOI: 10.1016/0736-5748(92)90010-w
|View full text |Cite
|
Sign up to set email alerts
|

The structural and neurochemical development of the fetal guinea pig retina and optic nerve in experimental growth retardation

Abstract: In this study we have examined structural and neurochemical aspects of retinal and optic nerve development in experimentally growth-retarded fetal guinea pigs following maternal unilateral artery ligation. Eye weight (n = 4) and total retinal area (n = 6) at 62 days gestation (term approximately 66 days) were both relatively spared when expressed as a percentage of body weight but in absolute terms were significantly reduced by 18% (P less than 0.001) and 13% (P less than 0.05) respectively when compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
(7 reference statements)
2
17
0
Order By: Relevance
“…Brain weight was also reduced in experimental animals but was relatively spared when compared to controls as evidenced by the increased brain:body and brain:liver ratios. These results are comparable to previous findings (Lafeber et al, 1984;Nitsos and Rees, 1990;Rees and Bainbridge, 1992), however a result not reported previously was a significant reduction in the brainstem weight in GR compared to control fetuses. It is known from previous work that these GR fetuses are chronically hypoxic, malnourished (Jones and Parer, 1983), and have an altered endocrine balance (Jones et al, 1987).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Brain weight was also reduced in experimental animals but was relatively spared when compared to controls as evidenced by the increased brain:body and brain:liver ratios. These results are comparable to previous findings (Lafeber et al, 1984;Nitsos and Rees, 1990;Rees and Bainbridge, 1992), however a result not reported previously was a significant reduction in the brainstem weight in GR compared to control fetuses. It is known from previous work that these GR fetuses are chronically hypoxic, malnourished (Jones and Parer, 1983), and have an altered endocrine balance (Jones et al, 1987).…”
Section: Discussionsupporting
confidence: 92%
“…The results show that there was no significant difference in the number of motor neurons in the hypoglossal nucleus of GR compared to control fetuses, a finding which confirms previous studies on the trochlear nucleus of GR sheep ) and on retinal ganglion cells in GR guinea pigs (Rees and Bainbridge, 1992). As the counts are made at the end of the period of cell death, it is possible that a reduction in neurogenesis has been compensated for by a reduction in programmed cell death.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The observed reduction in axonal area in subjects with IUGR may reflect either reduced axonal growth with a reduction of axonal volume or a decrease in the number of axons, i.e., in the number of neurons. Experimentally growth restricted fetal guinea pigs had signs of delayed myelination with a reduced density of myelinated axons in the optic nerve when examined shortly before term (17). In addition, these changes were accompanied by a reduced width of cellular layers in the retina and an unaffected number of neurons in the ganglion cell layer (higher density but reduced retinal area), suggesting a reduction in the growth of the neuropile.…”
Section: Discussionmentioning
confidence: 98%